The dynamics of social competence in the last decade: A research of Lithuanian students - Antinienė, D.; Lekavičienė, R. (Psichologija, 2012)
According to the dominant view of psychology, the construct of social competence is inseparable from the context, it is action and activity-oriented and related to the specific goals and transactions of personality. Social competence determines the level of efficiency of social behaviour. Social competence of personality is one of the main factors influencing psycho-social adaptation of personality. The survey, performed in the period of 1998–1999, revealed some peculiarities of social competence of Lithuanian students. In the survey, performed in 2010–2011, it was tried to find out whether social environment, which changed in these times, and its requirements for a young person had an impact to the changes of social competence, or, more precisely, to the change of priorities of social skills, which are one of the indicators of social competence. The students from different Lithuanian universities participated in the surveys: in the first survey participated 623 students and in the second survey participated 590 students. In the surveys Ullrich and de Muynck social competence assessment questionnaire (Ullrich and de Muynck, 1998, adapted by Lekavičienė, 1999), which analyses the behaviour according seven factors – (F1) General self-confidence, (F2) Resistance to failures and criticism, (F3) Ability of expressing feelings, (F4) Ability of asking for a favour, (F5) Unyielding, (F6) Ability of demanding, (F7) Feeling not guilty, was used. On purpose to test the psychometric validity of social competence assessment questionnaire, in 2010–2011 the analysis of the reliability of scales was performed repeatedly. Internal consistency of the scales of social competence assessment questionnaire (Cronbach’s alpha varied from 0,6 to 0,8 in both surveys), resolution (itt), minimal and maximal intercorrelation between the items of every scale were re-tested. In conclusion it can be predicated that the psychometric quality of Ullrich and de Muynck social competence assessment questionnaire after the second measurement was good. Data analysis revealed that some particular changes of students’ social skills, reflecting the level of social competence, happened in the last decade: students became more self-confident, decisive and less dependent on other people, they are capable to express their feelings more spontaneously. Equally, contemporary young people are less used to ask other people for a favour or for some information and that can be related to both positive reasons, i.e. to higher self-confidence, and to negative reasons, for example, to the fear of repulse or commitment to other people. During the analysis of the whole structure of social competence assessment questionnaire the method of multidimensional scales allowed to make the sequence of scales in which two aspects are reflecting – emotional strain, experienced by a person at the time of realisation of social skills and the inner or outer plan of realisation of a social skills.